Fenomena Perilaku Seksual â€œAyam Kampusâ€ Di Kota Semarang - Rimawati, Eti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Background: Phenomenon of â€œCampus Chickenâ€ was analogues to an iceberg phenomenon where the ice on the surface seems less visible but underneath there are many more. Sexual behavior are symbolic that influence how we think about ourselves, how we relate with others and how others relate and think about us. This study aims to examine sexual behavior of â€œcampus chickenâ€ in Semarang city. Method: The research design was qualitative exploration with cross sectional approach. Sampling techniques used snowball chain sampling, obtained six respondents. Collecting data used by indepth interview. Triangulation method was Focus Group Discussion (FGD, and In-depth interview to informant. Analyzing method used thematic analysis. Results: Base on the collected data, there are five themes namely Self Concept, Language, Socialization, Sexual Script and Safe Sex Behavior. Most of respondents valued themselves as friendly individual, attractive performance and accept â€œcampus chickenâ€ called. Socialization had effect to permissive behavior between women and men. Most of respondents considered the society culture and norms (cultural scripts), in selecting place, time and people have a goal to provide environmental suitability to community (interpersonal scripts) and what will be done, with what people like, safe sex behavior and the what sexual activity (intra psychic scripts). Safe sex behavior was shown by using condom and routine health checking to gynecologist. The importance of life skill was to develop self esteem and self concept, counseling service, entrepreneurship skills and partnership to become major programs to overcome this problem.